2021
DOI: 10.1002/jgh3.12684
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with time to clinical remission in pediatric luminal Crohn's disease: A retrospective cohort study

Abstract: The funders did not participate in the work. We do not have any financial disclosures or conflicts of interest to mention. Author contribution: Samuel Sassine conceptualized and designed the study, designed data collection instruments, collected data, carried out the initial analyses, drafted the initial manuscript, reviewed, and revised the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…To obtain early MH and maintain sustained MH, patients with an SES-CD greater than 11.5 at baseline should be treated more aggressively with biologics. Because some more severe patients could combine IFX with EEN to induce remission, it has been reported that the combination of EEN and TNFα inhibitors was associated with faster clinical remission ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain early MH and maintain sustained MH, patients with an SES-CD greater than 11.5 at baseline should be treated more aggressively with biologics. Because some more severe patients could combine IFX with EEN to induce remission, it has been reported that the combination of EEN and TNFα inhibitors was associated with faster clinical remission ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A significant bias must be considered because patients who are slow to go into the first remission are followed afterward for a shorter period in a pediatric setting before their transfer to adult care. However, we have demonstrated in a past study that patients with high levels of inflammatory markers (CRP, FC, and erythrocyte sedimentation rate) reached clinical remission faster (29). In this study, patients in clinical remission with increased CRP and FC levels were at a greater risk of relapse, which could explain the association between shorter time to remission and higher risk of relapse.…”
Section: Discussionmentioning
confidence: 91%
“…Clinical variables at diagnosis included age; patient's sex; weight, height, and body mass index z-scores; PCDAI (24); and Paris classification of CD, clinical symptoms, extraintestinal manifestations, and time to the first clinical remission (either continuously in days or categorized with a cutoff level of 12 weeks based on a study that demonstrated that being in clinical remission at 12 weeks after induction was predictive of steroid-free remission at 1 year (28)). We defined clinical remission as the resolution of clinical symptoms, that is, defined by a sPCDAI score of <10 (29).…”
Section: Methodsmentioning
confidence: 99%